2023
DOI: 10.1007/s00170-023-11163-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of hatch-spacing variation in a lack-of-fusion defect prediction criterion for laser-based powder bed fusion processes

Abstract: Lack of fusion (LOF) defects impact adversely on the mechanical properties of additively manufactured components produced via laser-based powder bed fusion. Following a stress-relieving heat treatment, the tensile properties and hardness of Ti6Al4V components were found to be negatively impacted by the presence of LOF defects. This work considers a geometrical-based inequality for the prediction of LOF defects. We critically evaluate an LOF criterion using both the experimentally and analytically obtained melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…[ 89 ] The primary purpose of utilizing the VED is to characterize the empirical observations obtained from LPBF experiments. [ 90,91 ] The formulation begins by considering the most crucial process parameters in the following mannerVED=PVht$$V E D = \frac{P}{V h t}$$…”
Section: Effect Of Process Parameters On Vibrational Characteristics ...mentioning
confidence: 99%
“…[ 89 ] The primary purpose of utilizing the VED is to characterize the empirical observations obtained from LPBF experiments. [ 90,91 ] The formulation begins by considering the most crucial process parameters in the following mannerVED=PVht$$V E D = \frac{P}{V h t}$$…”
Section: Effect Of Process Parameters On Vibrational Characteristics ...mentioning
confidence: 99%
“…The defects can be located either by destructive or non-destructive postprocessing techniques. In destructive, manufactured samples are cross-sectioned at certain locations, and then by using metallographic procedures the samples are prepared and the defects are captured using optical imaging [8]. In Non-Destructive Testing (NDT), the X-ray Computed Tomography (X-CT) of the sample is carried out to locate the defects within the manufactured components [9].…”
Section: Imaging Defectsmentioning
confidence: 99%
“…The study found that the testing method not only detected the defects but also helped in characterising the shape and size of defects. Harkin et al [8] used both NDT and the destructive characterisation method to capture the lack of fusion defects. In NDT, XCT scan, and destructive characterisation, the optical imaging method was used.…”
Section: Imaging Defectsmentioning
confidence: 99%
“…On the other hand, if the energy is too high, keyhole porosity defects can occur. 33,34 Lack of fusion defects are identified by the unmelted powders and can be aligned perpendicular to (lack of fusion between layers) or parallel to the building direction (lack of fusion between scan tracks). According to Yang et al, 11 irregularly shaped defects with unmelted regions are sometimes aligned either perpendicular or parallel to the building direction due to a lack of fusion.…”
Section: Introductionmentioning
confidence: 99%
“…If the energy density is insufficient, lack of fusion defects may form. On the other hand, if the energy is too high, keyhole porosity defects can occur 33,34 …”
Section: Introductionmentioning
confidence: 99%